2019
DOI: 10.54771/bsj.v1i3.77
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Intensitas Kebisingan Dengan Keluhan Auditori Pada Pekerja Bagian Produksi Pabrik Fabrikasi Baja

Abstract: Kebisingan telah lama menjadi perhatian dan permasalahan di tempat kerja. Tingkat intensitas kebisingan yang melebihi NAB dapat menimbulkan gangguan kesehatan seperti gangguan pendengaran. Tujuan dari penelitian ini adalah untuk mengetahui adanya hubungan tingkat intensitas kebisingan dengan keluhan auditori. Penelitian ini bersifat analitik dengan pendekatan cross-sectional. Populasi berjumlah 100 pekerja bagian produksi pabrik fabrikasi baja, sampel sebanyak 80 pekerja dengan teknik pengambilan sampel simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies that have been carried out include general hospital area in Surabaya (Arifianto, 2017), manufacturing industry in Malang (Sholihah et al, 2019), small muffler industry in Purbalingga (Risvianni et al, 2019), and industrial forest plantation in North Sumatera (Muhdi, 2022). The research of Minggarsari & Sahuri (2019) concluded that there is a relationship between noise intensity and auditory complaints among workers in the production division of PT X Bogor 2019. According to Wahyudi (2018), the noise level in the industrial area of PT.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that have been carried out include general hospital area in Surabaya (Arifianto, 2017), manufacturing industry in Malang (Sholihah et al, 2019), small muffler industry in Purbalingga (Risvianni et al, 2019), and industrial forest plantation in North Sumatera (Muhdi, 2022). The research of Minggarsari & Sahuri (2019) concluded that there is a relationship between noise intensity and auditory complaints among workers in the production division of PT X Bogor 2019. According to Wahyudi (2018), the noise level in the industrial area of PT.…”
Section: Introductionmentioning
confidence: 99%